Estrogen receptor beta expression in prostate adenocarcinoma - Asgari Mojgan; Morakabati Arman (BMC, 2011)
Abstract Background Prostate cancer is the most commonly diagnosed cancer in men and the second leading cause of cancer death in men. Estrogen induction of cell proliferation is a crucial step in carcinogenesis of gynecologic target tissues, and there are many studies recently done, showing that prostate cancer growth is also influenced by estrogen. The characterization of estrogen receptor beta (ER-b) brought new insight into the mechanisms underlying estrogen signalling. In the present study, we investigated the expression of estrogen receptor-b (ER-b) in human prostate cancer tissues. Methods We selected 52 paraffin-embedded blocks of prostate needle biopsies in a cross-sectional study to determine frequency and rate of ER-b expression in different grades of prostate adenocarcinoma according to Gleason grading system. Immunohistochemical staining of tissue sections by monoclonal anti ER-b antibody was performed using an Envision method visualising system. Results ER-b expression was seen in tumoral cells of prostatic carcinoma in all 29 cases with low and intermediate tumors (100%) and 19 of 23 cases with high grade tumor (83%). Mean rate of ER-b expression in low & intermediate grade cancers was 68.41% (SD = 25.63) whereas high grade cancers showed 49.48% rate of expression (SD = 28.79). Conclusions ER-b expression is reduced in high grade prostate cancers compared to low & intermediate grade ones (P value 0.027).